Biochemical And Micro-Mineral Status Of Yak (Poephagus Grunniens L.) Reared Under High Altitude Traditional Migratory System (Applied Biological Research, 2012)
The present study was conducted on thirty apparently healthy adult yaks of either sex reared under traditional migratory free range system of  rearing. Blood samples were analyzed for normal hematology, serum  biochemical parameters and micro-mineral status of yaks when grazed in  summer grazing ground and winter grazing ground. Hemoglobin content  in yaks in summer grazing grounds was significantly (P0.01) higher than  that of animals in winter pastures. Red blood corpuscle (RBC) counts,  white blood cell (WBC) counts, erythrocytic sedimentation rate (ESR)  and packed cell volume (PCV) in yaks were similar in both summer and  winter pasture. Similarly, no significant difference was observed in any of  the biochemical parameters studied. The mean cobalt and zinc values in  blood were significantly higher in animals grazing in summer grazing  ground than those in winter grazing ground. However, the mean copper  value was lower than the critical value indicating possible Cu deficiency.
Keywords: Biochemical analysis; blood; haematology; high altitude; migratory system; physiological response; trace element; yak